Malaysian children’s attitudes towards television advertising - Abd Ghani, Noor Hasmini; M. Zain, Osman (Emerald Group Publishing Limited, 2004)
Explores the attitudes of children in Malaysia’s competitive children’s market towards TV advertising, and how this affects their spending; children influence the market as immediate consumers, as influencers of their parents and other people, and as future adult consumers.Outlines the objectives and methodology of new quantitative research conducted into predictors of children’s attitudes, which also includes the effect of children’s attitudes on parents; the current research involved two primary schools in the Jitra town area, with a total of 252 children.Gives the background of child attitude research since Piaget, and explains the Rossiter scale.Identifies children’s preferences in products, themes and types of TV advertising.Finds that children’s awareness of advertising, and the influence on parents’ purchase decisions, are important predictors of child attitudes to advertising; the influence of TV advertising does impinge on consumer behaviour, whether of children or of their parents as a result of pestering, and younger children and children from lower social classes are especially susceptible to TV advertisements.